LEGAL RECONSTRUCTION OF IMPLEMENTATION LEGALLY BINDING VERDICT IN INDUSTRIAL RELATIONS COURT - Sri Gilang Muhammad Sultan Rahma Putra (Jurnal Hukum dan Peradilan, 2020)
The existence of industrial relations courts until now still can not provide adequate legal protection to justice seekers. This article begins with the existing legal problems in the form of not implemented legally binding of industrial relations court verdicts. The unapplied verdicts have resulted in the exclusion of the rights of justice seekers. This paper identifies the problem related to normative perspective and provide solutions through legal reconstruction from the normative view. Then, the problems are examined using normative legal research methods based on statute approach and historical approach as well as case approach. By examining several research results it is known that the legal vacuum which regulates sanctions against those who do not intend to enforce industrial relations court rulings that have legal force still need to be addressed immediately to guarantee the rights of the seekers of justice in the industrial relations court. This paper recommends to establish a Supreme Court Regulation on the implementation of institutional force on industrial relations disputes cases and the need for amendment of Law Number 2 Year 2004 on Industrial Relations Dispute Settlement.